Rodents in agriculture and public health in Malawi: Farmers’ knowledge, attitudes, and practices - Donga, Trust Kasambala; Bosma, Luwieke; Gawa, Nyson; Meheretu, Yonas (Frontiers in Agronomy, 2022)
Given that rodents are responsible for nearly 280 million cases of undernourishment worldwide and that about 400 million people are affected by rodent-associated zoonoses annually, management of rodent populations that are agricultural pests and/or reservoirs of pathogens is a major food security and public health matter. In sub-Saharan Africa, the median crop loss due to rodents is about 16% in the field and about 8% during storage. The impact on public health is not well-established albeit >60 zoonotic diseases can be spread to humans via rodents. Therefore, focusing on rodent-related community knowledge, attitudes, and practices is crucial to establishing robust baseline information as a springboard for future targeted studies. The study was conducted in September 2020 in Lilongwe and Nkhata Bay districts in Central and Northern Malawi, respectively. A semi-structured questionnaire, focus group discussions, and interviews with key informants were used. Farmers reported rodents were a major problem for staple crops (maize, rice, and cassava) and the main species responsible were the Natal multimammate mouse (Mastomys natalensis), silver mole-rat (Heliophobius argenteocinereus), and house mouse (Mus musculus domesticus). Awareness of rodent-associated health risks is very low as exemplified by reports of rodent human bites, eating rodent-contaminated food, and processing and consumption of wild rodents in poor hygienic conditions, and these practices were flourishing when Malawi was a bubonic plague endemic country. Rodent management is less practiced, and when practiced, it is symptomatic. It is considered a matter of individual households and typically relies on the use of rodenticides and insecticides without proper dosage and user instructions. We recommend rigorous campaigns to create better awareness among the public regarding the impacts of rodents on agriculture and community health and the need for community engagement for effective rodent management. A paradigm shift is needed by adapting/adopting practices of ecologically-based rodent management and reducing dependency on synthetic chemicals.